Application time of Wedelia trilobata leaf extract as a bioherbicide for controlling dominant weeds in soybeans - Faisal Abdillah; Dyah Weny Respatie; Aziz Purwantoro (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2026)
Wedelia leaf extract at a 40% concentration has been reported as an effective bioherbicide for inhibiting the growth of Cyperus rotundus, a dominant weed in soybean cultivation; however, information regarding the most effective application timing remains unavailable. Consequently, this study aimed to determine the optimal application time of Wedelia (Wedelia trilobata L.) leaf extract as a bioherbicide to control dominant weeds, specifically broadleaf weed (Tridax procumbens L.) and purple nutsedge (Cyperus rotundus L.), in soybean crops. The research employed a split-plot design, where the main plots consisted of the plant species (Tridax procumbens, Cyperus rotundus, and soybean), while the subplots consists of three application timings: 7 days before planting (D-7), at the time of planting (D0), and 7 days after planting (D+7), which were then compared against a C0- (negative control=without treatment) and a C0+ (positive control=using the chemical herbicide Pendimethalin (application within 7 days before planting) with dose 3 L ha-1). The results indicated that 7 days before planting (D-7) was the most effective time for applying the 40% Wedelia leaf extract in inhibiting the growth of Tridax procumbens and Cyperus rotundus in soybean cultivation. Keywords: Cyperus rotundus; timing application; Tridax procumbens; weed control